A history of travel in 50 vehicles - Grey, Paula (History in 50, 2016)
"Paula Grey explores how creative thinkers--sometimes collaborating, sometimes competing, and always building on the work of their predecessors--have envisioned new ways to move about in the world. From the first foot migration out of Africa to the Model T Ford, hot air balloons, submarines, rickshaws, and moon rockets, humans have combined imagination, daring, and scientific and technical knowledge to improve existing vehicles or create new ones. Geography, culture, and available technologies have all influenced the development and use of vehicles in different parts of the world, and human travel has, in turn, often had a profound influence on society and the environment"--Provided by publisher.